Impact of vitamin D supplementation on arterial vasomotion, stiffness and endothelial biomarkers in chronic kidney disease patients. - Nihil Chitalia; Tuan Ismail; Laura Tooth; Frances Boa; Geeta Hampson; David Goldsmith; Juan Carlos Kaski; Debasish Banerjee (PLoS ONE)
Background Cardiovascular events are frequent and vascular endothelial function is abnormal in patients with chronic kidney disease (CKD). We demonstrated endothelial dysfunction with vitamin D deficiency in CKD patients; however the impact of cholecalciferol supplementation on vascular stiffness and vasomotor function, endothelial and bone biomarkers in CKD patients with low 25-hydroxy vitamin D [25(OH)D] is unknown, which this study investigated. Methods We assessed non-diabetic patients with CKD stage 3/4, age 17-80 years and serum 25(OH)D <75 nmol/L. Brachial artery Flow Mediated Dilation (FMD), Pulse Wave Velocity (PWV), Augmentation Index (AI) and circulating blood biomarkers were evaluated at baseline and at 16 weeks. Oral 300,000 units cholecalciferol was administered at baseline and 8-weeks. Results Clinical characteristics of 26 patients were: age 50±14 (mean±1SD) years, eGFR 41±11 ml/min/1.73 m2, males 73%, dyslipidaemia 36%, smokers 23% and hypertensives 87%. At 16-week serum 25(OH)D and calcium increased (43±16 to 84±29 nmol/L, p<0.001 and 2.37±0.09 to 2.42±0.09 mmol/L; p = 0.004, respectively) and parathyroid hormone decreased (10.8±8.6 to 7.4±4.4; p = 0.001). FMD improved from 3.1±3.3% to 6.1±3.7%, p = 0.001. Endothelial biomarker concentrations decreased: E-Selectin from 5666±2123 to 5256±2058 pg/mL; p = 0.032, ICAM-1, 3.45±0.01 to 3.10±1.04 ng/mL; p = 0.038 and VCAM-1, 54±33 to 42±33 ng/mL; p = 0.006. eGFR, BP, PWV, AI, hsCRP, von Willebrand factor and Fibroblast Growth Factor-23, remained unchanged. Conclusion This study demonstrates for the first time improvement of endothelial vasomotor and secretory functions with vitamin D in CKD patients without significant adverse effects on arterial stiffness, serum calcium or FGF-23. Trial registration ClinicalTrials.gov NCT02005718.